An automated vacuum infusion process for manufacturing high-quality fiber-reinforced composites. (1st April 2023) - Wang, Tongtong; Huang, Kai; Guo, Licheng; Zheng, Tao; Zeng, Fanlin
Abstract: A new vacuum infusion process called Automatically Controlled Pressure Vacuum Infusion (ACPVI) was proposed to improve product quality and reduce material and process variabilities by using process automation and combining the advantages of two vacuum infusion processes—Vacuum-Assisted Process (VAP) and Controlled Atmospheric Pressure Resin Infusion (CAPRI). An automated vacuum infusion workstation was designed and constructed. Processing parameters were monitored, including laminate thickness, resin mass, mold temperature, and resin trap and infusion bucket pressures. The ACPVI reduced fabric relaxation during filling and thermal expansion of laminate and increased resin shrinkage compared with the VAP and CAPRI. The ACPVI increased the fiber volume fraction of laminate compared with the VAP and CAPRI. The ACPVI decreased the void content on the inlet side compared with the CAPRI. Compared with the VAP and CAPRI, the ACPVI significantly improved product quality, indicating its potential for manufacturing high-quality fiber-reinforced composites, such as aerospace parts.